Implementation of Islamic Ethics in Pharmaceutical Services: A Literature Review Approach - Diski Wahyu Wijianto; Ahda Maulida Ulufan Nurinnafi'a; Anisah Luthfitah; Muhammad Wildan Firdaus; Sastyana Suryandaru; Rizkina Elistya Febriani (Walidem Institute and Publishing, 2023)
Pharmacy services require a solid moral foundation in addition to technical skills. In situations like this, the application of Islamic ethics in pharmaceutical practice becomes relevant and important. Excavating Islamic moral principles that cover spiritual, social, and human aspects, this article discusses the close relationship between Islamic ethics and pharmaceutical service. Pharmacists need to provide fair and dignified service to Islamic moral values. Islamic values include sincere intentions, strong beliefs, prevention of damage, justice, privacy, and professional development. In addition, the spiritual aspect is emphasized, given the importance of spirituality in the lives of Muslim patients. The data search method is used through online journals through the use of sources such as Google Scholar, ScienceDirect, Web Of Science, Scopus, and Elsevier, by conducting journal reviews over the past 15 years. This article emphasizes the importance of Islamic ethics education and training in pharmaceutical practice and stresses that pharmacists who understand Islamic Ethics better can help patients better, guarantee quality of service, and address complex ethical issues. It is recognized that the effective application of Islamic ethics in the pharmaceutical industry requires cooperation between the public, pharmacists, and other health professionals. It is expected that public awareness of the importance of Islamic ethics can shape a positive attitude toward pharmaceutical services and encourage adherence to ethical principles. Despite obstacles such as the lack of support for spiritual care and the limitations of knowledge, the future offers a great opportunity to develop extensive pharmaceutical practices that are consistent with Islamic moral values. This can be achieved through improved education, clear ethical guidelines, and interprofessional collaboration. The application of Islamic ethics in pharmaceutical services can be a solid foundation for comprehensive and dignified health care.